2017
DOI: 10.3390/genes8100275
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of TALE Homeobox Genes in the Endangered Fern Vandenboschia speciosa

Abstract: We report and discuss the results of a quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis of the expression patterns of seven three amino acid loop extension (TALE) homeobox genes (four KNOTTED-like homeobox (KNOX) and three BEL1-like homeobox (BELL) genes) identified after next generation sequencing (NGS) and assembly of the sporophyte and gametophyte transcriptomes of the endangered fern species Vandenboschia speciosa. Among the four KNOX genes, two belonged to the KNOX1 class an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
(123 reference statements)
1
6
0
Order By: Relevance
“…Thus, Tables S2 and S3 contain those transcripts that are homologous to genes involved in the vegetative to reproductive transition in flowering plants (487 transcripts) and those homologous to genes involved in the genetic control of plant development in flowering plants (5968 transcripts). Additionally, Table S4 lists the transcripts representing transcription factors (1084 transcripts), with special interest in those that regulate plant development such as MADS box or Homeobox genes [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Tables S2 and S3 contain those transcripts that are homologous to genes involved in the vegetative to reproductive transition in flowering plants (487 transcripts) and those homologous to genes involved in the genetic control of plant development in flowering plants (5968 transcripts). Additionally, Table S4 lists the transcripts representing transcription factors (1084 transcripts), with special interest in those that regulate plant development such as MADS box or Homeobox genes [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it regulated tomato fruit development [28]. Currently, the TALE gene family has been found in many plants: 33 AtTALE genes in A. thaliana, 40 LjTALE genes in Lotus japonicas K. [63], 46 GaTALE genes in Gossypium arboretum L., 47 GrTALE genes in G. raimondii L., 88 GbTALE genes in G. barbadense L., 94 GhTALE genes G. hirsutum L. [8], and 35 PtTALE genes in poplar [64], 7 VsTALE genes in Vandenboschia speciose G. [16]. Therefore, the copy number of the TALE gene family in different species is different.…”
Section: Discussionmentioning
confidence: 99%
“…Except for some homeobox genes, TALE encodes an atypical structure forming two helices and three additional amino acid residues (P-Y-P) [9][10][11]. The TALE family plays a vital role in regulating plant growth and development [12][13][14][15], regulating the sporophyte program [16], the formation of plant meristems [7], and the maintenance of organ morphology [17], organ position [18], hormone regulation [19], signal transduction [20] and tuber formation [21]. Studies have shown that BELL and KNOX proteins specifically recognize and bind to form the BELL-KNOX heterodimer protein [22], which is essential for the nuclear localization of two transcription factor proteins and the activity of binding target gene [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The homeobox gene is a transcriptional regulator that encodes the homeodomain (HD), which is widely found in eukaryotes. The typical HD consists of 60 amino acids, which can form a 3-helical domain in space [1][2][3]. However, there are some exceptions, such as the TALE (Three Amino-acid Loop Extension) gene families, which encode an atypical DNA binding domain consisting of 63 amino acids, with three additional amino acid residues (P-Y-P) inserted between the first and second helices [3].…”
Section: Introductionmentioning
confidence: 99%
“…sativum, Medicago truncatula, Camellia chekiangoleosa and five legume species[2][3][4][5][32][33][34][35][36]. Extensive studies have shown that gene replication, including tandem, fragment and genome-wide replication, not only plays an important role in genome rearrangement and amplification, but also in gene function diversification and gene families expression[37].…”
mentioning
confidence: 99%